The Extent of Damage to Live Stands in Sago Forests due to Logging in Ihamahu and Rumahkay, Maluku - Probo Santoso; Rochmad Hidayat; Wisnu Hasan; Rasyied Ichwan B; Alifa Diah Ayu Sekar (Jurnal Ilmu Ilmu Kehutanan, 2023)
It is feared that the natural growth of sago is unable to keep up with the high intensity of logging. Therefore, sago forest stands need to be managed properly and planned by organizing effective and efficient harvesting to minimize damage to live stands. The purpose of this study was to analyze the impact of logging on the damage of live stands. This research was conducted in Maluku Province, during October - December 2022. Data were collected by observing logging activities, measuring trees and making measuring plots with a size of 20 m x 20 m to measure damage to live stands. The results showed that the level of damage to live stands in the conventional logging system was higher at 31.82% when compared to controlled logging with a value of 12.42%. The productivity of controlled logging was higher than conventional logging. The level of damage to live stands and logging productivity in sago stands is highly dependent on the logging system carried out.